Efficiency Analysis of State Budget on Agricultural Development in Indonesia 2012-2016 - Salama, Sri Cahyaning Umi (Universitas Airlangga, 2018)
Indonesia is still far behind compared to other Asian countries in agriculture. The technology and the availability of pre-facilities are still inadequate because of the many obstacles that hamper agricultural development. Agricultural development is a major component of rural development. One way to help the process of agricultural development is with the ease of access to finance. The State through the Ministry of Agriculture continues to make efforts in encouraging the development of domestic agriculture. Funds distributed are not small so it is necessary to calculate the efficient use of state budget funds in agricultural development in Indonesia. This study aims to measure the level of efficiency of the state budget for the agricultural sector. The data used are secondary data derived from the Ministry of Agriculture's financial report from 2012 to 2016. The method used is Data Envelopment Analysis (DEA) with input oriented and output oriented with Variable Returns to Scale (VRS). The input variable used is the realization of State Budget (APBN) for agriculture sector, while the output variables used are Farmer's Exchange Rate (NTP), Gross Domestic Product, and Farmer Productivity. The results show that the year 2015 becomes a very inefficient year both in terms of input oriented and output oriented. The increase in the realization of state expenditures for agriculture is not balanced by significant results, even in 2016 where the relatively small increase in the realization of the agriculture sector budget has had a comparable impact. Keywords: Efficiency, realization Budget expenditure, agricultural development